2011
DOI: 10.1088/0004-637x/744/2/148
|View full text |Cite
|
Sign up to set email alerts
|

CANDELS: CONSTRAINING THE AGN-MERGER CONNECTION WITH HOST MORPHOLOGIES ATz∼ 2

Abstract: Using HST /WFC3 imaging taken as part of the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS), we examine the role that major galaxy mergers play in triggering active galactic nuclei (AGN) activity at z ∼ 2. Our sample consists of 72 moderate-luminosity (L X ∼ 10 42−44 erg s −1 ) AGN at 1.5 < z < 2.5 that are selected using the 4 Msec Chandra observations in the Chandra Deep Field South, the deepest X-ray observations to date. Employing visual classifications, we have analyzed the rest-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
369
6
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(415 citation statements)
references
References 68 publications
36
369
6
4
Order By: Relevance
“…It seems that AGN evolution is dominated by a nonmerger process. Other studies about AGN hosts reach similar conclusions, such as Kocevski et al (2012), Santini et al (2012), and Schawinski et al (2011). Their results provide evidence that the starburst galaxies only account for 10% of the cosmic SFR density at z ∼ 2 (Rodighiero et al 2011;Lamastra et al 2013).…”
Section: Introductionsupporting
confidence: 64%
“…It seems that AGN evolution is dominated by a nonmerger process. Other studies about AGN hosts reach similar conclusions, such as Kocevski et al (2012), Santini et al (2012), and Schawinski et al (2011). Their results provide evidence that the starburst galaxies only account for 10% of the cosmic SFR density at z ∼ 2 (Rodighiero et al 2011;Lamastra et al 2013).…”
Section: Introductionsupporting
confidence: 64%
“…The SEDS fields are also covered by CANDELS (Cosmic Assembly Near-Infrared Deep Extragalactic Legacy Survey; Grogin et al 2011), which has obtained deep, highresolution HST imaging at 1 to 1.6 microns with HST WFC3 in portions of these fields. Recent CANDELS results have found that, for X-ray selected AGN, the fraction of irregular and disturbed host galaxies is no greater than that of a control sample (Kocevski et al 2012). In contrast to the X-ray selected sample, our SEDS variability survey finds a significant number of mid-IR variability-selected AGN in disturbed galaxy hosts or those having irregular morphology compared to a control sample of galaxies at similar mass and redshift (Figure 2).…”
Section: Mid-ir Variability Surveys For Agncontrasting
confidence: 57%
“…The rest frame U -V colors of the mid-IR variable host galaxies are distributed through the "green valley" and, similar to the optical variables, several lie in the blue, star-forming region of the galaxy color-magnitude diagram. Kocevski et al 2012) while the magenta bars represent mid-IR variability selected AGN (non-shaded regions) compared to a control sample of galaxies with the same mass distribution for each sample (gray bars in each section). While overall morphologies of the hosts are largely similar, mid-IR variability detected AGN are more likely to reside in irregular/disturbed host galaxies than the control group contrasting with the X-ray detected AGN sample.…”
Section: Mid-ir Variability Surveys For Agnmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent observations of AGN host morphologies and colors have suggested that major mergers probably do not fuel most low and intermediate-luminosity AGN, as a large fraction appear in "normal" disks (Gabor et al 2009;Schawinski et al 2011;Cisternas et al 2011;Kocevski et al 2012;Rosario et al 2011;Civano et al 2012;Santini et al 2012;Mullaney et al 2012;Treister et al 2012). This should perhaps not be surprising.…”
Section: Introductionmentioning
confidence: 99%